The innovator's way : essential practices for successful innovation - Denning, Peter J. , 1942-; Dunham, Robert (MIT Press, 2010)
'Innovation is the ruling buzzword in business today. Technology companies invest billions in developing new gadgets; business leaders see innovation as the key to a competitive edge; policymakers craft regulations to foster a climate of innovation. And yet businesses report a success rate of only four percent for innovation initiatives. Can we significantly increase our odds of succeeding at innovation? In The Innovator's Way, innovation experts Peter Denning and Robert Dunham reply with an emphatic yes. Innovation, they write, is not simply an invention, a policy, or a process to be managed. Innovation is a personal skill that can be learned, developed through practice, and extended into organizations. Denning and Dunham define innovation as the art of getting people to adopt change. They draw a distinction between invention and innovation: many inventions never become innovations, and many innovations do not involve an invention. They identify and describe eight personal practices that all successful innovators perform: sensing, envisioning, offering, adopting, sustaining, executing, leading, and embodying. Together, these practices can boost a fledgling innovator to success. Weakness in any of these practices, they show, blocks innovation. Denning and Dunham describe innovation at scales ranging from the private (a family organization of chores and allowances) to the planetary (the invention and adoption of the World Wide Web). They provide a detailed account of the eight practices and how to accomplish them; and they chart the path to innovation mastery, from individual practices to teams and social networks.'--Provided by publisher